2019
DOI: 10.1002/ppp.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cliff retreat of permafrost coast in south‐west Baydaratskaya Bay, Kara Sea, during 2005–2016

Abstract: Recent years of increasing air temperature in the Arctic have led to a significant increase in the rate of retreat of permafrost coast, which has threatened livelihoods and infrastructure in these areas. The Kara Sea hosts more than 25% of the total Arctic coastline. However, little is known about how coastal erosion in the Kara Sea may have changed through time, and the climatic and environmental drivers remain unclear. Here we study coastal dynamics along a 4-km stretch of permafrost and sea-ice-affected coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The crest retreat to the left of the mouth of the Sabryavpenzya River was measured to be 9.1 m during the period of 2016-2017 [12]. This part of the coast has higher frozen bluffs (14 m) than the bluffs in Case #1, and the slope of the bluff face is almost vertical.…”
Section: Case #2: Crest Retreat During the Summer Of 2017mentioning
confidence: 96%
See 2 more Smart Citations
“…The crest retreat to the left of the mouth of the Sabryavpenzya River was measured to be 9.1 m during the period of 2016-2017 [12]. This part of the coast has higher frozen bluffs (14 m) than the bluffs in Case #1, and the slope of the bluff face is almost vertical.…”
Section: Case #2: Crest Retreat During the Summer Of 2017mentioning
confidence: 96%
“…The coastline of the Kara Sea is the longest among all the water bodies within the Arctic Ocean [10] and composes more than one-quarter of the total length of Arctic coastline [11]. Isaev et al [12] reported erosion rates as high as 29.1 m/year along the coast of the Kara Sea. The mean annual erosion rate along this coast is estimated to be in the range from 0.2 m to 2.0 m per year [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high ice content of the sediments and sea wave activity favored coastal retreat in the study area. During 2005–2014, wind‐driven ocean wave activity during the sea‐ice‐free period was shown to influence the magnitude of retreat more than recent temperature increase …”
Section: Methodsmentioning
confidence: 99%
“…Most of the recent Arctic coastal change studies concentrated on accelerated coastal erosion rates in locations spread 170 across the Arctic region and associated them with diminishing sea-ice extent, longer exposure to storm wave impacts, and thawing coastal permafrost (e.g Farquharson et al, 2018;Irrgang et al, 2018;. Gibbs et al, 2019;Isaev et al, 2019). Also, in glaciated parts of the Arctic, such as Greenland or Svalbard, coastal research focused on the response of coastal zone to increased delivery of glacial sediments (e.g Bendixen et al, 2017;Strzelecki et al, 2018)…”
mentioning
confidence: 99%